SLOW-STROKE BACK MASSASE TO PAIN INTENSITY OF RHEUMATID ARTHRITIS IN ELDERY - Melina Kartika Sari (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2014)
Introduction.Rheumatoid arthritis represented an autoimmune disease that attacks the joints causing chronic inflammation. Rheumatoid arthritis experienced by many elderly. One of non-pharmacological ways to overcome this pain was by stimulation of the skin with a technique of slow-stroke back massase. The purpose of this study was to analyse the effect of slow-stroke back massase to pain intensity of Rheumatic arthritis on eldery. Method. The research design in this study was Quasy Experiment with the approach of pre-test and post-test group with control. The sample consisted of 20 respondents selected by purposive sampling technique. And divided into two groups: experimental group (n = 10) and control group (n = 10). Data obtained by interview and observation method of pain intensity for 7 days. Then the processed data statistical test of Wilcoxon Signed Ranks test and Mann Withney test with a standard error of 0.05. Result. The results showed in the control group no change in pain intensity. While the majority of the experimental group (60%), pain intensity change from medium become mild. These results can be seen from statistical tests with the Wilcoxon Signed Ranks test resulted P value = 0.014 and Mann Withney post test resulted P value = 0.007, H0 rejected. Discussion. Based on the research results it can be concluded that there was influence of slow-stroke back massase toward the pain intensity of rheumatoid arthritis in elderly. Thus it can be an alternative to reduce the pain of rheumatoid arthritis in the elderly. Keywords: slow-stroke back massase, intensity of pain, rheumatoid arthritis, elderly